Microwave-assisted green synthesis of anilines, phenols, and benzenediamines without transition metals, ligands, or organic solvents - N. McConnell (Green Chemistry Letters and Reviews, 2018)
A novel, microwave-assisted method producing anilines and phenols from activated aryl halides is reported. This high-yielding method reduces current reaction requirements and removes organic solvents and catalysts making a more efficient and eco-friendly alternative for the synthesis of important pharmaceutical building blocks.